Beneficial Effects of Nebivolol in Comparison with Atenolol on Safety and Tolerability in Essential Hypertension - Vivek V. Bhosale; S.C. Inamdar; Karande V.B.; Burute S.R.; Murthy M.B.; Ghatak A. (Journal of Clinical and Diagnostic Research, 2014)
Introduction: Hypertension, “The silent killer” is a multifactorial disorder which is asymptomatic and if left untreated leads to lethal complications. Nebivolol is a third generation beta blocker with additional vasodilating property due to nitric oxide release. Aim: The current study aims to assess efficacy and safety of Nebivolol and compare with Atenolol. Materials and Methods: This was prospective, double blind, comparative controlled clinical study. Total 90 patients were enrolled into study as per selection criteria. Patients were randomized to receive Atenolol and Nebivolol with 45 patients in each group for 12 weeks. Results and Conclusion: The mean reduction diastolic blood pressure in Nebivolol and Atenolol group was 10.77±2.60 and 10.05±2.83 respectively. The number of patients with adverse effect events was higher in the Atenolol than in the Nebivolol group (36.84% of Atenolol Vs 12.82% of Nebivolol). Thus it can be concluded that, for the same antihypertensive effect, Nebivolol was better tolerated than Atenolol.